2009
DOI: 10.1038/leu.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Genomic approaches to small molecule discovery

Abstract: With the sequencing of the human genome and the development of new genomic technologies, biomedical discovery has been transformed. The applications of these new approaches are ever-expanding from disease classification, to identification of new targets, to outcome prediction. A logical next step is the integration of genomic approaches into small molecule discovery. This review will focus on the application of genomics to compound discovery, with an emphasis on the hematological malignancies. It will focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In light of these results, we prioritized TDZ2 and TDZ6 for in vivo testing. We evaluated neuroleptic effects by a stepped-dose test 29 in NSG mice treated with increasing doses of drug (1,5,8,10,12, and 15 mg/kg), and found that both the analogues TDZ2 and TDZ6 did not provoke akinesia, either at the dose where TDZ was efficient (at least 8 mg/kg), or at higher doses (n 5 3; Figure 6D). We finally selected TDZ6 as the analogue with the efficacy to prevent AML progression in vivo and found that it counteracted tumor growth at a dosage equivalent to TDZ, 8 mg/kg (n 5 5; Figure 6E), with the great possibility of potentiating the standard chemotherapy effect.…”
Section: Tdz Targets Mll-af6-aml Cytoskeleton Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of these results, we prioritized TDZ2 and TDZ6 for in vivo testing. We evaluated neuroleptic effects by a stepped-dose test 29 in NSG mice treated with increasing doses of drug (1,5,8,10,12, and 15 mg/kg), and found that both the analogues TDZ2 and TDZ6 did not provoke akinesia, either at the dose where TDZ was efficient (at least 8 mg/kg), or at higher doses (n 5 3; Figure 6D). We finally selected TDZ6 as the analogue with the efficacy to prevent AML progression in vivo and found that it counteracted tumor growth at a dosage equivalent to TDZ, 8 mg/kg (n 5 5; Figure 6E), with the great possibility of potentiating the standard chemotherapy effect.…”
Section: Tdz Targets Mll-af6-aml Cytoskeleton Dynamicsmentioning
confidence: 99%
“…9,10 High-throughput drug screening (HTDS) approaches are currently used to test whether novel compounds or drugs known to be active in other malignancies may be effective in acute leukemia, with the goal of introducing them rapidly into pediatric clinical trials. 7,11,12 We considered this strategy to prioritize the identification of drugs with therapeutic benefits against the childhood AML variant harboring the t(6;11)(q27;q23) chromosomal rearrangement, which defines a peculiar biological and clinical subset of AML, where the genes lysine methyltransferase 2A (KMT2A, MLL) and afadin (AFDN, AF6) are fused, generating the chimeric protein MLL-AF6. 13,14 We and other international groups previously identified MLL-AF6-rearranged AML as the most aggressive among the pediatric AMLs with MLL rearrangements, with a low probability of event-free survival, reported to range from 11% to 23% at 5 years.…”
Section: Introductionmentioning
confidence: 99%